Addressing the Obesity-Diabetes Continuum in Cambodia: A Critical Review of Health Policy, Regulation, and Care Delivery System Readiness - Yem Sokha; Kem Sokunthea; Tun Sreypeov (International Journal of Nursing Information, 2026)
Cambodia is undergoing a rapid epidemiological transition marked by an escalating continuum of obesity and type 2 diabetes mellitus (T2DM). This study evaluates Cambodia’s health policy responsiveness, regulatory frameworks, and care delivery system readiness to address this shifting chronic disease burden. Synthesizing national data from the Cambodia Demographic and Health Survey 2021–22 and the STEPS Survey 2023 alongside national strategic frameworks, this review provides a critical macro-level policy-linked analysis, filling a vital literature gap by bridging clinical epidemiology with health systems governance. Findings confirm a severe metabolic burden, with 31.7% of adult women overweight/obese, 15.2% experiencing abdominal adiposity, and T2DM prevalence reaching 6.4%. Crucially, 50% of T2DM cases remain undiagnosed, a systemic failure rooted in primary care unreadiness, diagnostic stockouts of HbA1c and lipid panels, and historical prioritization of acute infectious management. Socioeconomic disparities compound this risk, as individuals with no formal education exhibit the highest T2DM prevalence (11.2%). On the regulatory front, current fiscal policies like sugar-sweetened beverage taxation require aggressive strengthening, while financial frameworks like the Health Equity Fund lack preventative screening mandates. This review contributes a novel, multi-level evaluation framework that transitions Cambodia’s public health discourse from passive clinical reporting to active, systemic healthcare reorientation. Ultimately, mitigating this metabolic crisis demands restructuring primary care into chronic care models, expanding financial protection for preventative services, and enforcing multi-sectoral dietary regulations.